Authenticity of DNA in Proving Crime - Bentaya, Zoulikha; Kahloul, Sami (Journal of Legal Studies and Researches, 2020)
This paper aims to shed light on DNA and its evidentiary value before a criminal court, by addressing the most important uses of DNA in the criminal field and determine the binding force for this evidence.